Theoretical and methodological principles of enterprise’s financial restructuring - Lysenko, Marianna (My University, 2012)
In this article the author describes the various approaches to the definition of "financial restructuring", defines purpose, the main directions and stages of restructuring the financial type. The basic principles, which the process of financial restructuring are based on, are outlined. The characteristic of the basic mechanisms and particular methods of financial restructuring, features of its effects and effectiveness are characterized.У цій статті автор описує різні підходи до визначення поняття «фінансова реструктуризація», визначає цілі, основні напрями і етапи реструктуризації фінансового типу. Викладено основні принципи, на яких заснований процес фінансової реструктуризації. Наведена характеристика основних механізмів і конкретних методів фінансової реструктуризації, особливості його впливу та ефективності.
Keywords: financial restructuring; financial recovery of enterprises; фінансова реструктуризація; фінансове оздоровлення підприємств; финансовая реструктуризация; финансовое оздоровление предприятий; кафедра економіки праці та менеджменту